Esri ArcGIS Maps for Creative Cloud Extension. - Harmer, Tony (linkedin.com, 2020)
Learn how to design with data-driven maps inside Adobe Illustrator and Photoshop using the ArcGIS Maps for Creative Cloud extension from Esri.